Kutaisi And Newspaper “Shroma’’ - Koberidze, Mariam (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
The weekly political and literary newspaper “Shroma” was publishing Kutaisi in 1881-1893. The newspaper used to highlight the works of cultural and educational activities in Kutaisi of public figures - Dimitri Dadiani, Dimitri Nazarashvili, Bosleveli (Estate Mchedlidze), Kezeli, Davit Bakradze and Grigol Volski. Akaki Tsereteli and Kirile Lortkipanidze actively participated in the activity of the newspaper. Akaki Tsereteli’s publicistic letters dedicated to Kutaisi and texts of oratorical speech were often published in the newspaper “Shroma’’.The most notable among them are: ”On the Second Coming”, ”Remark regarding the theatre’’, “Nakudala,’’ ”About the clergy’’. “Kutaisi’’, “Few words About Lord Aleksandre Mikeladze, “Toe a woman supporting women”, “The Answer, “Mr. Editor”, “Kutaisi on May 19, 1882’’, “Our misfortune”, ,”Small Note”, “Note”, “To the Collectors of Public Poems and Stories, “Hot News”, “From travel stories”, “Remakrs related to Kutaisi”. We should remark that Akaki Tsereteli uses figurative terms to describe the real-life of Kutaisi of that period. For example, Quail Hunting’, Quail - self servingman; “hounds - henchmen of self-serving men; talk fest - parliament…